Українські допоміжні формування Збройних сил Німеччини у Києві в 1941–1943 рр.: структура, чисельність, діяльність - Дерейко, І. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2004)
The article describes the history of appearing and functioning of Ukrainian units of German Police, SD and Wehrmacht in Kyiv under occupation. These units made a largest part of armed forces around the city. They were carrying main weight in performing guard and police functions in the region, supporting occupation regime, which couldn’t do it by itself because of lack of personnel. Structure, armaments, subordination and activities of Ukrainian units, those completing and supplying principles, motivation of regular volunteers are also studied. Units’ operating outside of Kyiv in the last period of war and those soldiers’ postwar fate is overviewed.